Is Informed Consent Required for AI Diagnosis? Navigating the Legal and Ethical Landscape of Digital Health - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2022)
Is Informed Consent Required for AI Diagnosis? Navigating the Legal and Ethical Landscape of Digital Health The integration of Artificial Intelligence (...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Machine Learning